Aggregate-colonizing copepods in a glacial fjord: Population dynamics, vertical distribution and allometric scaling of growth and mortality rates of Microsetella norvegica and Oncaea spp. (September 2021) - Koski, Marja; Swalethorp, Rasmus; Kjellerup, Sanne; Nielsen, Torkel Gissel
Abstract: Most global analysis on the role of copepods in food web efficiency or carbon sequestration ignore the harpacticoid or poecilostomatoid copepods that are under-estimated in traditional zooplankton surveys and under-studied with respect to their ecology and behavior. Nevertheless, when small-mesh-size nets are used these groups appear to dominate zooplankton abundance and sometimes even biomass from Arctic to tropical seas. We studied the seasonal succession of abundance, body size, vertical distribution, reproduction, growth and mortality of two aggregate-colonizing copepods, Microsetella norvegica and Oncaea spp. in a glacial fjord, to investigate the allometric scaling of their vital rates and the correlation between their reproduction, mortality and vertical distribution and environmental variables. Although both species are known to feed on marine snow, they differed in population dynamics, vertical distribution and environmental tolerance. Also, in contrast to most sac-spawning copepods, both M. norvegica and Oncaea spp. had a high specific mortality of eggs and early naupliar stages, and the allometric scaling of their egg size and growth differed from calanoid and cyclopoid copepods. Our results suggest that these non-calanoid copepods do not necessarily share the same habitat or respond similarly to the environment, and that our understanding of the allometric scaling of copepods is incomplete if we do not consider these copepod groups. M. norvegica and Oncaea spp. form by virtue of their high abundance an important part of oceanic food webs, and should be included if we are to understand the future of the ocean ecosystems.